A Novel Approach for Preparation and In Situ Tensile Testing of Silica Glass Membranes in the Transmission Electron Microscope - Mačković, Mirza; Przybilla, Thomas; Dieker, Christel; Herre, Patrick; Romeis, Stefan; Stara, Hana; Schrenker, Nadine; Peukert, Wolfgang; Spiecker, Erdmann (Frontiers in Materials, 2017)
The mechanical behavior of glasses in the micro- and nanometer regime increasingly gains importance in nowadays modern technology. However, suitable small-scale preparation and mechanical testing approaches for a reliable assessment of the mechanical properties of glasses still remain a big challenge. In the present work, a novel approach for site-specific preparation and quantitative in situ tensile testing of thin silica glass membranes in the transmission electron microscope (TEM) is presented. Thereby, advanced focused ion beam techniques are used for the preparation of nanoscale dog bone-shaped silica glass specimens suitable for in situ tensile testing. Small amounts of gallium are detected on the surface of the membranes resulting from redeposition effects during the focused ion beam preparation procedure. Possible structural changes of silica glass upon irradiation with electrons and gallium ions are investigated by controlled irradiation experiments, followed by a structural analysis using Raman spectroscopy. While moderate electron beam irradiation does not alter the structure of silica glass, ion beam irradiation results in minor densification of the silica glass membranes. In situ tensile testing of membranes under electron beam irradiation results in distinctive elongations without fracture confirming the phenomenon of superplasticity. In contrast, in situ tensile testing in the absence of the electron beam reveals an elastic/plastic deformation behavior and finally leads to fracture of the membranes. The Young’s moduli of the glass membranes pulled at beam-off conditions in the TEM are comparable with values known for bulk fused silica, while the tensile strength is in the range of values reported for silica glass fibers with comparable dimensions. The impact of electron beam irradiation on the mechanical properties of silica glass membranes is further discussed. The results of the present work open new avenues for dedicated preparation and nanomechanical characterization of silica glass and further contribute to a fundamental understanding of the mechanical behavior of such glasses when being scaled down to the nanometer regime.